Optimizing Family-Based Home Care to Improve the Quality of Life of Patients with Chronic Diseases - Lestari Lona Lolo; Dewiyanti Dewiyanti; M. Khalid Fredy Saputra (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2026)
Introduction: Chronic diseases remain a major public health concern globally and in Indonesia, contributing significantly to morbidity, mortality, and decreased quality of life. Family involvement in home care has been identified as a key strategy to improve patient outcomes, yet many families lack adequate knowledge and skills to provide effective care. This study aimed to optimize family-based home care to improve the quality of life of patients with chronic diseases. Methods: This community service program involved 45 participants consisting of patients with chronic diseases and their family caregivers. A six-step intervention was implemented, including needs assessment, program planning, health education, caregiving skills training, mentoring, and evaluation. Data were collected using structured instruments to measure quality of life, medication adherence, and caregiving skills before and after the intervention. Results: The findings showed a significant improvement in all measured indicators. The mean quality of life score increased from 58.4 to 72.6, medication adherence improved from 61.3 to 78.9, and caregiving skills increased from 55.7 to 80.2. These results indicate that the intervention effectively enhanced both patient outcomes and family caregiving capacity. Conclusion: Optimizing family-based home care is an effective strategy to improve the quality of life of patients with chronic diseases. Strengthening family capacity through education, training, and continuous support can lead to sustainable improvements in home-based care.